Cellular response to short-time mechanical stimuli: mediating Ca2+ influx via PIEZO1 - Fuan Wang; Hongkun Chen; Zhongyuan He; Jianfeng Li; Zhengya Zhu; Tao Tang; Junhong Li; Jiaxiang Zhou; Qiuxiao Tan; Zhen Li; Martin J. Stoddart; Xizhe Liu; et al. (European Cells & Materials)
Physical activity shows a positive correlation with overall health, and vigorous intermittent lifestyle physical activity (VILPA) similarly offers advantages in reducing the risk of all-cause mortality. Might the short-time mechanical stimuli be discernible to cells, eliciting commensurate physiological responses? The study's objective was to investigate the cellular response to short-time mechanical stimuli. Human umbilical cord-derived mesenchymal stem cells (hUCMSCs), isolated and thoroughly characterized, were subjected to various stimuli, including activation and mechanical stretching, with Ca2+ influx assessed through alterations in fluorescence intensity. Further validation of these findings was confirmed through short hairpin RNA (shRNA) and inhibitors. In addition, a comprehensive examination of PIEZO1 alterations was conducted through quantitative real-time polymerase chain reaction (qRT-PCR) and western blot (WB) techniques. The results shown different frequencies of stretching stimulation and durations induced varying degrees of Ca2+ influx. The most substantial increase occurred within 2–3 minutes in the group subjected to 0.5 Hz stretching for 2 minutes (p < 0.05). Stretching at 0.5 Hz resulted in significant elevation in PIEZO1 mRNA expression at 15 minutes and 1 hour. Additionally, stretching cause a gradual rise in PIEZO1 protein levels, with a notable peak observed at 2 hours. In conclusion, cells primarily sense short-time mechanical stimuli through PIEZO1, predominantly mediated by regulated Ca2+ influx. This underscores PIEZO1's crucial role in cellular responsiveness to transient mechanical cues, advancing our understanding of mechanosensory mechanisms in cellular physiology.